Accurate voltage prediction for lithium and sodium-ion full-cell development - Yongxiu Chen; Yazid Lakhdar; Lin Chen; Brij Kishore; Jaehoon Choi; Ethan Williams; Dimitra Spathara; Roksana Jackowska; Emma Kendrick (Next Energy)
The cell balance, negative to positive (N:P) electrode ratio, and voltage limits determine the first cycle loss and reversible capacity at different rates and can influence degradation mechanisms and cycle life. This balance needs optimizing for each cell chemistry, electrode mass loading, and cell format, typically performed through empirical optimization. This work provides an accurate predictive tool for calculating full-cell voltages by decoupling the independent electrode potential under the same operating conditions. Full-cell NMC622//Graphite voltages are accurately predicted from low-rate half-cell voltage profiles (pseudo-open circuit voltages) and validated for different N:P ratios, rates, material types, and cell formats. The application of this methodology to several chemistries, including sodium-ion cell chemistry, high power (NMC622//MoNb12O33), and high energy (NMC920305//Graphite-SiOx), is also demonstrated. In addition, each electrode's key thermodynamic and kinetic parameters are extracted from the observed voltage and overpotentials for the negative and positive electrodes at different rates. Elucidating the rate-limiting electrodes and providing further cell balancing information to achieve high power, energy, and lifetime. The extracted parameters can be used in multi-scale models to optimise cell design and performance limitations further. This method promises new and quicker routes for cell optimization for different chemistries and formats.